‘Solidarity of Action:’ Is Africa Reclaiming Its Historic Role as the Center of Palestinian Solidarity? - Baroud, Ramzy (SETA Foundation, 2024)
Solidarity against the colonial regime is one of the keys to overcoming the oppressor. This is why the 20th century, which is seen as the century of decolonization, experienced many demonstrations of solidarity from Africa to America. Palestine’s long resistance against the Israeli colonial project should be considered as another decolonization movement. Unfortunately, many Arab regimes have not shown solidarity with Palestine in recent years. While the Arab states have hesitated to show full solidarity, it is the African continent that has stepped in, internationalizing the debate regarding genocide. This is, indeed, not limited to Africa. South American states also show their support for Palestine and have halted their relations with Israel. How do we make sense of this solidarity, from Namibia to South Africa and from Nicaragua to Cuba? This commentary analyzes the evolution of Global South solidarity with Palestine since the foundation of Israel, with a more focused focus on the African continent. It demonstrates that as decolonial nations, African states have once again shown their solidarity with Palestine, even though there have been some hesitant times due to realpolitik and the U.S. role in protecting Israel’s status.
Keywords: Africa; Palestine; Israel; Solidarity; Colonialism; Global South; South Africa; Genocide